Antenatal corticosteroids for women at risk of imminent preterm birth in low-resource countries: the case for equipoise and the need for efficacy trials. Issue 3 (30th August 2017) - Vogel, Joshua P; Oladapo, Olufemi T; Pileggi-Castro, Cynthia; Adejuyigbe, Ebunoluwa A; Althabe, Fernando; Ariff, Shabina; Ayede, Adejumoke Idowu; Baqui, Abdullah H; Costello, Anthony; Chikamata, Davy M; Crowther, Caroline; Fawole, Bukola; et al.
Abstract : The scientific basis for antenatal corticosteroids (ACS) for women at risk of preterm birth has rapidly changed in recent years. Two landmark trials—the Antenatal Corticosteroid Trial and the Antenatal Late Preterm Steroids Trial—have challenged the long-held assumptions on the comparative health benefits and harms regarding the use of ACS for preterm birth across all levels of care and contexts, including resource-limited settings. Researchers, clinicians, programme managers, policymakers and donors working in low-income and middle-income countries now face challenging questions of whether, where and how ACS can be used to optimise outcomes for both women and preterm newborns. In this article, we briefly present an appraisal of the current evidence around ACS, how these findings informed WHO's current recommendations on ACS use, and the knowledge gaps that have emerged in the light of new trial evidence. Critical considerations in the generalisability of the available evidence demonstrate that a true state of clinical equipoise exists for this treatment option in low-resource settings. An expert group convened by WHO concluded that there is a clear need for more efficacy trials of ACS in these settings to inform clinical practice.